Chemotherapy Side Effects and Their Correlation with Self-Concept Disruption in Cancer Patients - Setyobudi, Yustina Emi; Sakti, Ifa Pannya (Adult Health Nursing Journal, 2024)
Introduction: Chemotherapy, while an effective cancer treatment, often brings significant side effects that can negatively impact patients' psychological well-being, including their self-concept. This issue is critical, as a disturbed self-concept may influence patients' overall health and their response to treatment. Objectives: This study aims to determine the relationship between the side effects of chemotherapy and self-concept disturbances in cancer patients. Methods: This research employed a descriptive correlational design using a cross-sectional approach. The population consisted of cancer patients undergoing chemotherapy in January 2016. Data collection used structured questionnaires measuring both the severity of chemotherapy side effects and the level of self-concept disturbance. The Chi-Square test was used for data analysis with a significance level of 5% (α = 0.05). Results: The majority of respondents (83%) experienced severe side effects of chemotherapy, and 67% of them showed negative disturbances in self-concept. The statistical test revealed a significant relationship between chemotherapy side effects and self-concept disturbance (p = 0.015), indicating that patients with more severe side effects tend to have more disturbed self-concepts. Conclusions: There is a significant relationship between the side effects of chemotherapy and self-concept disturbance among cancer patients. These findings highlight the importance of psychological support and counseling in cancer care to help patients maintain a positive self-concept during treatment.